ChemInform Abstract: Flow Chemistry: Recent Developments in the Synthesis of Pharmaceutical Products. Issue 10 (February 2016) - Porta, Riccardo; Benaglia, Maurizio; Puglisi, Alessandra
Abstract: Review: [73 refs.